2018
DOI: 10.1113/ep087067
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery wall mechanics in young males with high cardiorespiratory fitness

Abstract: The influence of cardiorespiratory fitness on arterial stiffness in young adults remains equivocal. Beyond conventional measures of arterial stiffness, two-dimensional strain imaging of the common carotid artery (CCA) provides new information related to the intrinsic properties of the arterial wall. Therefore, the aim of this study was to assess the effect of cardiorespiratory fitness on both conventional indices of CCA stiffness and two-dimensional strain parameters, at rest and after a bout of aerobic exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…Although several previous studies have demonstrated that regular exercise attenuates the age-related increase in β-stiffness and aPWV (Tanaka et al, 2000;Vaitkevicius et al, 1993), those investigating the effect of exercise in young, healthy individuals report far less consistent results (Heydari et al, 2013;Kakiyama et al, 2005;Montero et al, 2017;Pugh et al, 2018;Tanaka et al, 2000). However, the findings of the present study imply that,like PCS and S-SR, the positive influence of habitual exercise on E p , β-stiffness and aPWV is similar in young and middle-aged males.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Although several previous studies have demonstrated that regular exercise attenuates the age-related increase in β-stiffness and aPWV (Tanaka et al, 2000;Vaitkevicius et al, 1993), those investigating the effect of exercise in young, healthy individuals report far less consistent results (Heydari et al, 2013;Kakiyama et al, 2005;Montero et al, 2017;Pugh et al, 2018;Tanaka et al, 2000). However, the findings of the present study imply that,like PCS and S-SR, the positive influence of habitual exercise on E p , β-stiffness and aPWV is similar in young and middle-aged males.…”
Section: Discussioncontrasting
confidence: 89%
“…Power analyses of CCA 2D‐Strain parameters were conducted a priori by sampling data from two separate studies, one investigating the effect of ageing on 2D‐Strain parameters in untrained individuals (Bjällmark et al., 2010) and the other investigating the effect of high CRF on 2D‐Strain parameters in young men (Pugh et al., 2018). A mean difference in PCS of 3.8% (Cohen's d effect size = 4.19) was detected between young and old individuals, whereas a mean difference of 2.3% ( d = 0.7) was detected between highly and moderately fit young men.…”
Section: Methodsmentioning
confidence: 99%
“…Myocardial deformation like torsion/twist, and Carotid-Artery-Longitudinal-Motion (CALM) as well as two-dimensional arterial circumferential strain are amongst those novel parameters. For example, it is possible that one-dimensional measurements like cIMT and conventional measures of local stiffness miss adaptations at distinct regions of the arterial wall circumference that can only be captured by a full 360 • assessment like circumferential strain and strain rate [18,19]. The addition of CALM measurements has the potential to determine the impact of altered carotid structure on arterial wall mechanics [20].…”
Section: Future Directionsmentioning
confidence: 99%
“…Speckle-tracking ultrasonography (STE) has been applied to the assessment of circumferential strain (ɛ) and strain rate (SR) of the common carotid artery (CCA). [1][2][3][4][5] Originally developed for echocardiography, 6 the analysis of ɛ is tethered to key points of the electrocardiogram (ECG). Thus, to prevent measurement drift STE software assumes no deformation (i.e 0% ɛ) at the start of the cardiac cycle defined by the QRS wave.…”
mentioning
confidence: 99%
“…All images were acquired by the same sonographer using a Vivid IQ ultrasound machine with a 6-13 MHz linear transducer (GE Healthcare, Cambs, UK), at 106.9 fps. Images were analysed as previously detailed 1,3,5 using EchoPac software (GE Healthcare, Cambs, UK). The resulting data files were further analysed by applying a 1000-point cubic spline to either the ɛ or SR data, which was used to identify raw and corrected peak ɛ (outlined below), and TTP.…”
mentioning
confidence: 99%